TINGKAT INFLASI DAN RASIO LIKUIDITAS TERHADAP RESIKO SAHAM SYARIAH - Suparno Suparno (Program Magister Akuntansi Unsyiah, 2010)
The purpose of this study is to examine the effect of inflation and liquidity ratio simultanously and partially on the risk level of syariah stocks of public companies registered in Indonesia Stock Exchange (BEI).The research population is all shariah companies listed in Jakarta Islamic Index (JII) from January 2004 to December 2005 continuously and they report their financial statement at that period. As a result, there are only 15 companies used for further analysis. The hypothesis testing confirms that the level of inflation and liquidity ratio affect simultaneously as well as partially on risk of syariah stocks with regression coefficient β1= 5,767 and β2= -0.018. Keyword: Inflation ratio, liquidity ratio and risk rate of syariah stock